发布网友
共1个回答
热心网友
(1)设数列{an}的公差为d,数列{bn}的公比为q,
则an=1+(n-1)d,bn=2qn-1,
由b1b3=b4,得q=b4b3=b1=2.
由b2s2=16=2q(2+d),解得d=2.
∴an=2n-1,bn=2n.
(2)∵T2n+1=c1+a1+(a2+b1)+a3+(a4+2b2)+…+a2n-1+(a2n+nbn)
=1+S2n+(b1+2b2+…+nbn).
令A=b1+2b2+…+nbn.
则A=2+2?2+3?23+…+n?2n,
2A=22+2?23+…+(n-1)?2n+n?2n+1.
∴-A=2+22+…+2n-n?2n+1=2×(1?2n)1?2-n?2n+1;
∴A=n?2n+1-2n+1+2.
又S2n=2n(1+a2n)2=4n2.
∴T2n+1=1+4n2+n?2n+1-2n+1+2=3+4n2+(n-1)2n+1.
∴T2n+1-13n-(2n-2)bn=3+4n2+(n-1)2n+1-13n-(2n-2)?2n=3+4n2-13n.
令3+4n2-13n=0?n=3或n=14.
令3+4n2-13n<0?14<n<3;
令3+4n2-13n>0?n<14或n>3.
又因为n是正整数,
所以:当n=1或2时T2n+1-13n<(2n-2)bn;
n=3时,T2n+1-13n=(2n-2)bn;
当n>3时,T2n+1-13n>(2n-2)bn.
热心网友
(1)设数列{an}的公差为d,数列{bn}的公比为q,
则an=1+(n-1)d,bn=2qn-1,
由b1b3=b4,得q=b4b3=b1=2.
由b2s2=16=2q(2+d),解得d=2.
∴an=2n-1,bn=2n.
(2)∵T2n+1=c1+a1+(a2+b1)+a3+(a4+2b2)+…+a2n-1+(a2n+nbn)
=1+S2n+(b1+2b2+…+nbn).
令A=b1+2b2+…+nbn.
则A=2+2?2+3?23+…+n?2n,
2A=22+2?23+…+(n-1)?2n+n?2n+1.
∴-A=2+22+…+2n-n?2n+1=2×(1?2n)1?2-n?2n+1;
∴A=n?2n+1-2n+1+2.
又S2n=2n(1+a2n)2=4n2.
∴T2n+1=1+4n2+n?2n+1-2n+1+2=3+4n2+(n-1)2n+1.
∴T2n+1-13n-(2n-2)bn=3+4n2+(n-1)2n+1-13n-(2n-2)?2n=3+4n2-13n.
令3+4n2-13n=0?n=3或n=14.
令3+4n2-13n<0?14<n<3;
令3+4n2-13n>0?n<14或n>3.
又因为n是正整数,
所以:当n=1或2时T2n+1-13n<(2n-2)bn;
n=3时,T2n+1-13n=(2n-2)bn;
当n>3时,T2n+1-13n>(2n-2)bn.